Effect of the combined use of Esomeprazole and Imipenem against Pseudomonas aeruginosa - Islam, Tariqul; Mamun, Abdullah Al; Sarker, Debashish; Ahsan, Sunjukta; Kabir, Md Shahidul (Bangladesh Journal of Microbiology, 2018)
Antimicrobial activity of esomeprazole (0.25 mM) and imipenem (30 μg/ml) was tested independently and in combination against planktonic and biofilm associated cells of Pseudomonas aeruginosa. Esomeprazole (0.25 mM) and imipenem (30 μg/ml) were added to broth media in test tubes to determine their effect on growth of Pseudomonas aeruginosa at 2, 4, 6, 24 and 72 hours after inoculation at 37°C. Viable bacterial counts (cfu/ml) were measured by dilution and plating on nutrient agar medium and the biomass was measured at 600 nm using a spectrophotometer. Biomasses of bacterial biofilms were determined by tube adherence assay and measuring the absorbance at 580 nm wavelength. Pseudomonas aeruginosa showed decreased growth and biomass of sessile bacteria (p<0.05) after exposure to imipenem and esomeprazole compared to untreated controls after 48 and 72 hours of exposureat 37°C. However, the reduction in viable cells after exposure to esomeprazole was not significant after 48 and 72 hours of incubation at 37°C (p>0.05). Biomass of bacterial biofilms were significantly reduced after exposure to esomeprazole and imipenem compared to untreated controls (p<0.05) as determined by tube adherence assay. Esomeprazole and imipenem demonstrated antibacterial and anti-biofilm property against planktonic and biofilm embedded cells of P. aeruginosa which may be useful for treatment of bacterial infections. Bangladesh J Microbiol, Volume 34 Number 1 June 2017, pp 21-25